Psychology of Well-Being Theory, Research and Practice - Vella-Brodrick, Dianne; Steger, Michael
Psychology of Well-Being: Theory, Research and Practice ceased to be published by SpringerOpen as of 31st December 2016. SpringerOpen will continue to host an archive of all articles previously published in the journal and all articles published in Psychology of Well-Being during its time with SpringerOpen will remain fully searchable via the SpringerOpen website (https://www.springeropen.com/).